A impugnação do direito de propriedade como direito fundamental - Reato, Talissa Truccolo (2018)
The investigation questions if property rights can be considered a fundamental right. The first aim is to define fundamental rights, so that concepts and fundamentals are presented, highlighting the dignity of the human person. The following chapter proposes the examination of the explanatory elements of the property right from the concept, the fundamentals, the historical evolution and the social function of the property. In this fragment, the right to property is questioned in the list of fundamental rights according to the theories of Luigi Ferrajoli (which conditions property in the list of patrimonial rights) and Gregorio Peces-Barba (which justifies the disregard of property as a fundamental right for reasons of scarcity). The final topic examines the situation of fundamental rights and the condition of property rights in Brazil. In addition, a case of possible social consequences of the right to property as a fundamental right is attested from a concrete case. The relationship between the content of the research and the associated research line (Constitutional Jurisdiction and Democracy) is the support in the theory of fundamental rights. Methodologically it can be said that the logical bases of this research is conducted by means of the hypothetical -deductive scientific method, in relation to the approach is a qualitative investigation, relative to nature is basic, regarding the objectives the analysis in comment is exploratory and the procedure method is monographic.